Similar Is Not the Same – Mate Recognition in a Parasitoid Wasp - Jungwirth, Stefan; Ruther, Joachim; Pokorny, Tamara (Frontiers in Ecology and Evolution, 2021)
Finding and recognizing a suitable mate is a key prerequisite to reproductive success. Insects often recognize prospective mates using chemical cues and signals. Among these, cuticular lipids commonly serve for mate recognition at close range. The lipid layer on the surface of insects is comprised predominantly of cuticular hydrocarbons (CHCs), though more polar compounds may also be present. While the composition of the cuticular profile is typically species specific, many species additionally show differentiation between the sexes by sex specific compounds and/or compound ratios. It is often assumed that a clear sexual dimorphism of cuticular lipid profiles is a prerequisite for a potential function as sex pheromones. Both, sex specific single compounds or the profiles as a whole have been shown to serve as sex pheromones in parasitoid wasps. Here, we studied parasitoid wasps of the species Tachinaephagus zealandicus (Encyrtidae, Hymenoptera). Chemical analyses revealed that this species presents a case where males and females produce the same set of CHCs in similar relative amounts. To test whether these wasps nonetheless can use the cuticular lipids for close-range mate recognition, we tested the reaction of males towards freeze-killed conspecifics. Males showed copulation behavior exclusively towards dead females, but not towards dead males. Dead females from which the cuticular lipids had been removed did not elicit copulation behavior by tested males. Reapplication of female whole body extracts restored bioactivity, and males reacted with copulation attempts as often as towards the freeze-killed females. Bioassays with lipid fractions revealed that only the CHC fraction was bioactive on its own. Here, again, males reacted to female, but not to male CHCs. Our results indicate that these wasps are capable of using CHCs for close range sex recognition despite the similarity of male and female profiles.